Bridging Research and Practice: Using Article Analysis to Prepare Practitioners for Research-Informed Practice - Tatjana Dragovic (Izzivi Prihodnosti, 2024)
Research Question (RQ): Could a critical analysis of a few relevant research articles prepare practitioners for designing a research-informed improvement of own practice?